Gambaran Pola Diit Jumlah, Jadwal, dan Jenis (3J) pada Pasien dengan Diabetes Melitus Tipe 2 - Muhamad Ridlo; Juan Farustine Khasanah; Gusrina Komara Putri (Politeknik Karya Husada, 2021)
Background: DM type 2 is caused by an unhealthy diet. Dm type 2 human DNA test results from diit 3j to control blood sugar levels. Purpose: get an idea of diite patterns of number, schedule and type on patients with type 2 diabetes mellitus. Method: study USES a quantitative descriptive. The population used by dm type 2 sufferers with large sample 51 respondents who fit the criteria of inclusion using a total sampling technique. Data is collected using a questionnaire from the medical administrative study (MOS) questionnaires of patient patients developed through jotform and distributed online through the whatssapp group. The data analysis in this study uses univariate analysis using SPSS 23. Results: show that exact amounts of food amount to 31 or 60.8%, the exact type as many as 36 respondents or 70.6%, and the exact schedule of 31 or 60.8%. Conclusion: detailed pattern of diitics, the type and amount of food as appropriate as eating a heavy meal and interval interval of three hours, followed the list of foodchangers encouraged by the dietitian and restricted food intake.